(untitled) (Tanzania Medical Journal, 2009)
An 85 year old male presented at Bugando Medical centre with history and physical examination suggestive of prostatic carcinoma. The diagnosis of benign enlargement of the prostate was made based on sonography and PSA level. TURP was done and the prostate chips were sent for histology. Histology showed caseous necrosis and few epithelioid granulomas and langerhan's giant cells. Ziehl-Neelsen stain was positive for acid fast bacilli. The diagnosis of tuberculous prostatitis was made with no other foci of infection. Chest x ray, spine x rays and sonography of kidneys were normal. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 33-34